On the Relationship Between Molecular Mass and Anticoagulant Activity in a Low Molecular Weight Heparin (Enoxaparin) - Bendetowicz, Ana-Victoria; Pacaud, Elisabeth; Béguin, Suzette; Uzan, André; Hemker, H Coenraad (Thrombosis and Haemostasis, 1992)
A low molecular weight heparin (enoxaparin, mean molecular weight ~ 4,400) was separated by gel chromatography into eight different fractions with a narrow distribution around the following mean molecular weights: 1,800, 2,400, 2,900, 4,200, 6,200, 8,600, 9,800 and 11,000. We compared the influence of enoxaparin on the generation of thrombin in plasma to that of the eight fractions.We determined: a) the % of material with high affinity to antithrombin III (HAM) and the % of HAM above the critical chainlength necessary to allow for thrombin inhibition (ACLM), b) the specific catalytic activity on the decay of endogenous thrombin, and c) the inhibition of over-all thrombin formation in the extrinsic and the intrinsic pathway. From b and c we calculated the inhibition of prothrombin conversion in these pathways.We found that a) there is a gradual decrease of the HAM fraction with decreasing molecular weight; b) the specific catalytic activity for the inactivation of thrombin does not vary significantly between the fractions when expressed in terms of ACLM; c) the potency to inhibit prothrombin conversion does not vary significantly between the fractions when expressed in terms of HAM.